عصرنة تسيير الموارد البشرية بقطاع الصحة العمومية - رمضانى, حمزة; بن غنام, لخضر (جامعة الوادي - University of Eloued, 2023)
تعتبر الموارد البشرية أهم عنصر في جل المنظمات مهما كانت عامة أو خاصة، بحيث بدأ الاهتمام بالعنصر البشري في منتصف القرن العشرين تقريبا وهذا راجع إلى التطور السريع الذي عرفة المجال الصناعي بعد الحرب العالمية الثانية خاصة في الدول المتطورة صناعيا إلى إحداث طفرة نوعية في تحديد طبيعة ونوعية القوى العاملة أين يتم التركيز على اليد العاملة الأكثر معرفة والأكثر مهارة وتخصصا. فتطور أي مؤسسة مرتبط ومرهون بمدى تكوين وتدريب وتنمية موردها البشري وكيفية تسييره بالمفهوم الحديث يعتبر" الشريك الاجتماعي " الذي تتوقف عليه عمليات الإنتاج وفعالية المؤسسة من خلال أدائه لمجموعة من الوظائف وهذا لن يتم إلا وفقا عصرنة تسيير الموارد البشرية في المؤسسات العمومية. Abstract: Human resources are the most important element in most organizations, regardless of whether public or private, so that interest in the human element began around the middle of the twentieth century, due to the rapid development of the industrial field after World War II, especially in the industrially developed countries to create a qualitative breakthrough in determining the nature and quality of the workforce where the focus is on the most knowledgeable, skilled and specialized labor force. The development of an institution linked and dependent on the extent to which its human resource is formed, trained and developed and how it is conducted in the modern sense is the "social partner" on which production processes depend and the effectiveness of the institution through its performance of a range of functions, and this will only be done in accordance with the modernization of the management of human resources in public institutions.
التحديات والرهانات
مقال
Keywords: تسيير الموارد البشرية، العولمة، العولمة وإدارة الموارد البشرية; Human resources management, globalization, globalization and human resources management